2015
DOI: 10.1002/dc.23257
|View full text |Cite
|
Sign up to set email alerts
|

The application of the Johns Hopkins Hospital Template on urine cytology

Abstract: Background: To evaluate the utility of the Johns Hopkins Hospital Template in detection of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 12 publications
1
28
0
1
Order By: Relevance
“…There are some authors that use subcategories of atypia [4,[6][7][8] . However, Bostwick and Hossain [5] , in a very comprehensive study, found no use in stratifying urothelial cell atypia for diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…There are some authors that use subcategories of atypia [4,[6][7][8] . However, Bostwick and Hossain [5] , in a very comprehensive study, found no use in stratifying urothelial cell atypia for diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Samples classified as AUC-H, while unable to be definitively called high-grade urothelial carcinoma (HGUC), typically contain features highly predictive of HGUC, i.e., hyperchromasia, anisonucleosis, coarse clumped chromatin, irregular nuclear borders, and an increased nuclear-to-cytoplasmic (N/C) ratio [5] . Studies have tested these criteria and have found them to be easily reproducible and predictive of high-grade (HG) carcinoma in cytologic specimens [6,7] .…”
mentioning
confidence: 99%
“…The urine cytologic diagnoses of AUC‐H and HGUC are highly associated with high‐grade urothelial lesions . In our previous study, greater than one‐half of patients (58%) who had biopsy‐confirmed high‐grade urothelial lesions had a preceding cytologic diagnosis of AUC‐H or HGUC .…”
Section: Discussionmentioning
confidence: 83%
“…The goal of urinary cytology is to identify HGUC. In addition to its well‐defined cytologic features (such as hyperchromasia; a high nuclear:cytoplasmic ratio; an irregular nuclear membrane; anisonucleosis; and irregular, coarse, clumpy chromatin), HGUC also frequently demonstrates apoptosis with pyknotic nuclei and karyorrhexis in association with urinary cytologic examination of urothelial carcinoma . Apoptosis was observed more often in HGUC than low‐grade urothelial neoplasms in a small study of malignant atypical cells in urinary cytology .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation